Associations of incidental vertebral fractures and longitudinal changes of MR–based proton density fat fraction and T2* measurements of vertebral bone marrow - Leonhardt, Yannik; Ketschau, Jannik; Ruschke, Stefan; Gassert, Florian T.; Glanz, Leander; Feuerriegel, Georg C.; Gassert, Felix G.; Baum, Thomas; Kirschke, Jan S.; Braren, Rickmer F.; Schwaiger, Benedikt J.; Makowski, Marcus R.; et al. (Frontiers in Endocrinology, 2022)
Background: Quantitative magnetic resonance imaging (MRI) techniques such as chemical shift encoding-based water-fat separation techniques (CSE-MRI) are increasingly applied as noninvasive biomarkers to assess the biochemical composition of vertebrae. This study aims to investigate the longitudinal change of proton density fat fraction (PDFF) and T2* derived from CSE-MRI of the thoracolumbar vertebral bone marrow in patients that develop incidental vertebral compression fractures (VCFs), and whether PDFF and T2* enable the prediction of an incidental VCF. Methods: In this study we included 48 patients with CT-derived bone mineral density (BMD) measurements at baseline. Patients that presented an incidental VCF at follow up (N=12, mean age 70.5±7.4 years, 5 female) were compared to controls without incidental VCF at follow up (N=36, mean age 71.1±8.6 years, 15 females). All patients underwent 3T MRI, containing a significant part of the thoracolumbar spine (Th11-L4), at baseline, 6-month and 12 month follow up, including a gradient echo sequence for chemical shift encoding-based water-fat separation, from which PDFF and T2* maps were obtained. Associations between changes in PDFF, T2* and BMD measurements over 12 months and the group (incidental VCF vs. no VCF) were assessed using multivariable regression models. Results: Prior to the occurrence of an incidental VCF, PDFF in vertebrae increased in the VCF group (ΔPDFF=6.3±3.1%) and was significantly higher than the change of PDFF in the group without VCF (ΔPDFF=2.1±2.5%, P=0.03). There was no significant change in T2* (ΔT2*=1.7±1.1ms vs. ΔT2*=1.1±1.3ms, P=0.31) and BMD (ΔBMD=-1.2±11.3mg/cm^3 vs. ΔBMD=-11.4±24.1mg/cm^3, P= 0.37) between the two groups over 12 months. At baseline, no significant differences were detected in the average PDFF, T2* and BMD of all measured vertebrae (Th11-L4) between the VCF group and the group without VCF (P=0.66, P=0.35 and P=0.21, respectively). Conclusions: Incidental VCFs are associated with a significant longitudinal PDFF increase, while T2* and BMD show no significant changes prior to the occurrence of vertebral fractures. Therefore, a longitudinal increase in bone marrow PDFF may be predictive for vertebral compression fractures.